Analisis Kompetensi Guru Dalam Memanfaatkan Media Pembelajaran Berbasis Teknologi Dan Komunikasi (TIK) Di SMP 2 Bukittinggi - nurul atika dwi putri (At Turots: Jurnal Pendidikan Islam, 2023)
In Permendiknas 2007 number 16 there are four competencies that must be possessed by teachers including pedagogic, professional, individual and social competencies. Teacher competence in this study refers to competence. Pedagogically, in pedagogical competence means that teachers must know how to use and utilize ICT to learn. The purpose of this research is to describe teacher competence when using ICT-based learning media. The benefit of this research is a means to increase knowledge about the selection criteria and the use of ICT-supported learning media. The approach used in this research is descriptive qualitative type. Data collection techniques were observed and implemented for consultation. The subjects of this study were ICT teachers at SMP Negeri 2 Bukittinggi, class VIII. This research was conducted on November 2, 2022 at SMP Negeri 2 Bukittinggi. Based on the results of data analysis, it was found that teacher competencies related to science and technology mastery competencies, classroom management skills competencies and social and communication competencies, were not optimal. It is necessary to develop these competencies so that they will minimize the problems that exist in learning, so that the learning process can run better. In addition, teacher competence in utilizing technology-based learning media, information and communication at SMP Negeri 2 Bukittinggi is quite good in utilizing ICT-based learning media, but a lot of guidance is still needed in accessing media directly from the internet.